2016
DOI: 10.1007/s12182-016-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir stress path and induced seismic anisotropy: results from linking coupled fluid-flow/geomechanical simulation with seismic modelling

Abstract: We present a workflow linking coupled fluid-flow and geomechanical simulation with seismic modelling to predict seismic anisotropy induced by non-hydrostatic stress changes. We generate seismic models from coupled simulations to examine the relationship between reservoir geometry, stress path and seismic anisotropy. The results indicate that geometry influences the evolution of stress, which leads to stress-induced seismic anisotropy. Although stress anisotropy is high for the small reservoir, the effect of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Angus et al [15], Dancygier et al [19], and Kong et al [23] have carried out much work around the characteristics of stress arching, the evolution law of stress arch and the influencing factors of stress arch morphology and have made great progress. However, the existing results are mostly limited to the study of the development process of the arch structure, and there are few studies on the stability discrimination of the arch structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angus et al [15], Dancygier et al [19], and Kong et al [23] have carried out much work around the characteristics of stress arching, the evolution law of stress arch and the influencing factors of stress arch morphology and have made great progress. However, the existing results are mostly limited to the study of the development process of the arch structure, and there are few studies on the stability discrimination of the arch structure.…”
Section: Discussionmentioning
confidence: 99%
“…Its stability determines the composite rock pressure phenomena such as periodic weighting and strata behavior of the working face. In recent years, many scholars have studied the characteristics of stress arching [15][16][17][18], the evolution law of stress arch [19][20][21][22] and the influencing factors of stress arch morphology [23][24][25][26], and have achieved rich results. For example, Angus et al [15] studied the stress arch effect by coupling simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of numerical simulation method, Li [15] found a natural SA existed nearby the tunnel wall and used SA theory to establish an artificial SA by anchor bolt supporting to improve the stability of the underground chamber. Angus et al [16] studied the relationship between SA effect and seismic anisotropy through coupling simulation. The results indicated that the capabilities of the SA effect and two-side burdens that undertook loads restricted the overall change in effective stress and seismic anisotropy.…”
Section: State Of the Artmentioning
confidence: 99%